Budaya K-Pop dan Perubahan Perilaku Sosial Pada Mahasiswa Fakultas Ushuluddin Dan Studi Islam Universitas Islam Negeri Sumatra Utara - Afrida, Mauliani; Riza, Faisal; Kamal, Aulia (CV. ITTC INDONESIA, 2024)
The purpose of this study was to find out how the relationship between K-Pop culture and changes in social behavior in students of the Faculty of Ushuluddin and Islamic Studies, State Islamic University of North Sumatra. The results showed that K-Pop Culture can cause behavioral changes in students of the Faculty of Ushuluddin and Islamic Studies, namely: K-Pop is an inspiration and motivation for fans in the fashion world.By studying K-Pop Culture, fans (kpopers) know their selfimage and love themselves more. Furthermore, changes in terms of interaction, with the friendship between fans they have many friends from various regions or from outside countries.They can also socialize well. Fans are more independent, creative and innovative, such as learning Korean, opening an online shop by selling K-Pop things such as clothes, cosmetics, and others. The impact of K-Pop culture on consumerism varies, some fans buy goods related to their idols, everyone does not have the same opportunity to enjoy K-Pop goods. It did not cause a change in social strata because students of the Faculty of Ushuluddin and Islamic Stdusi were still able to balance between the needs and desires for goods related to K-Pop culture.